2007
DOI: 10.1128/jvi.00923-07
|View full text |Cite
|
Sign up to set email alerts
|

A Vectored Measles Virus Induces Hepatitis B Surface Antigen Antibodies While Protecting Macaques against Measles Virus Challenge

Abstract: Vaccines based on live viruses can be highly effective and easy to produce and deliver. Smallpox was eradicated with live vaccinia virus, and a live attenuated poliovirus vaccine has been at the core of the polio eradication campaign (17). Worldwide measles virus (MV) vaccination prevents an estimated 80 million cases and 4.5 million deaths annually (45) with minimal severe adverse effects, on average less than 10 in 1 million doses (34). With the currently recommended vaccination scheme, the first dose of vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
105
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 85 publications
(106 citation statements)
references
References 51 publications
1
105
0
Order By: Relevance
“…In current ovarian cancer, glioma, and myeloma clinical trials (38), patients cannot be in contact with unvaccinated infants or severely immunocompromised individuals until lack of shedding is established. Sheddingincompetent oncolytic viruses can be generated after transferring the EpR-inactivating mutations to a vaccine genetic background (39,40). We note that the MV vaccine strain has 1-way epithelial crossing characteristics even if it binds CD46, which is abundantly expressed apically and basolaterally in epithelia (13).…”
Section: Discussionmentioning
confidence: 97%
“…In current ovarian cancer, glioma, and myeloma clinical trials (38), patients cannot be in contact with unvaccinated infants or severely immunocompromised individuals until lack of shedding is established. Sheddingincompetent oncolytic viruses can be generated after transferring the EpR-inactivating mutations to a vaccine genetic background (39,40). We note that the MV vaccine strain has 1-way epithelial crossing characteristics even if it binds CD46, which is abundantly expressed apically and basolaterally in epithelia (13).…”
Section: Discussionmentioning
confidence: 97%
“…DI-RNAs may alter the characteristics of MV live-attenuated vaccines and modulate the efficacy of recombinant MV engineered for vaccination against heterologous pathogens or used as oncolytic vectors (27,(66)(67)(68). While vaccine producers seek to avoid DI-RNAs in order to standardize efficacy, oncolytic potency may not rely uniquely on efficient viral replication and cell lysis but may also rely on immunostimulatory properties (69,70).…”
Section: Discussionmentioning
confidence: 99%
“…(33). Similarly, subcutaneous vaccination of macaques with 10 4 infectious units of Moratenbased rMVs found that positions 3 and 6 induced equivalent immune responses for the parameters examined (34). However, another recent study showed that insertion of an ATU into positions 3 and 6 of a human parainfluenza virus 3 vaccine candidate caused a temperature-sensitive phenotype, resulting in attenuation of the virus in vivo (35).…”
Section: Fig 3 Target Cells Of Rmv Ez Egfp(3) Egfp Distribution In Mmentioning
confidence: 96%